2016
DOI: 10.1097/jcp.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravenous Methamphetamine Administration During Ibudilast Treatment

Abstract: Background Methamphetamine dependence is a significant public health concern without any approved medications for treatment. We evaluated ibudilast, a non-selective phosphodiesterase inhibitor, to assess the safety and tolerability during intravenous (IV) methamphetamine administration. We conducted a randomized, double-blind, placebo-controlled, within-subjects crossover clinical trial. Methods Participants received ibudilast (20 mg twice daily followed by 50 mg twice daily) and placebo, with order determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Whole striata (left and right sides) were flash frozen in ethanol/dry ice bath and stored at Ϫ80°C. Tissue were then shipped on dry ice to University of Utah Health Science Center for MA and amphetamine metabolite quantification as previously described (Slawson et al, 2002;DeYoung et al, 2016).…”
Section: Quantification Of Ma Metabolites Ma-treated Whole Striatal Tmentioning
confidence: 99%
“…Whole striata (left and right sides) were flash frozen in ethanol/dry ice bath and stored at Ϫ80°C. Tissue were then shipped on dry ice to University of Utah Health Science Center for MA and amphetamine metabolite quantification as previously described (Slawson et al, 2002;DeYoung et al, 2016).…”
Section: Quantification Of Ma Metabolites Ma-treated Whole Striatal Tmentioning
confidence: 99%
“…For this indication ibudilast has shown promise in clinical laboratory studies. Ibudilast was safe and well tolerated in combination with IV methamphetamine (DeYoung et al, 2016). Worley and colleagues (2016) examined whether ibudilast would reduce subjective effects of methamphetamine among non-treatment seeking, methamphetamine-dependent volunteers (n=11).…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…The trial showed that IBUD reduced tonic levels of alcohol craving (Ray et al, 2017a). Other research on IBUD has demonstrated its safety and initial efficacy for methamphetamine use disorder (DeYoung et al, 2016; Worley et al, 2016) and opioid use disorder (Cooper et al, 2016; Metz et al, 2017). IBUD, however, did not reduce tonic levels of high-fat/high-sugar food craving.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, placebo-control, human laboratory trial advanced IBUD development for alcohol use disorder (AUD) and found that IBUD reduced tonic levels of alcohol craving—and for individuals reporting higher levels of depressive symptoms—reduced the stimulant and rewarding effects of alcohol (Ray et al, 2017a). IBUD has similarly been studied for its safety and initial efficacy among individuals with methamphetamine use disorder (DeYoung et al, 2016; Worley et al, 2016) and opioid use disorder (Cooper et al, 2016; Metz et al, 2017). In sum, IBUD may be a promising pharmacotherapy for AUD and other substance use disorders.…”
Section: Introductionmentioning
confidence: 99%